Fish Protein Isolates Recovered from Silver Carp (Hypophthalmichthys molitrix) By-Products Using Alkaline pH Solubilization and Precipitation. Issue 3 (2nd April 2016) - Zhong, Saiyi; Liu, Shouchun; Cao, Jinxuan; Chen, Suhua; Wang, Weimin; Qin, Xiaoming
ABSTRACT: Fish protein isolates (FPI) were produced from silver carp processing by-products by means of the isoelectric solubilization-precipitation method, and the quality was evaluated. The alkali-aided process led to significantly more lipid reduction ( p < 0.05) compared with the acid-aided process. Similar protein types were extracted for the acid and alkali solubilization, and most protein types can be recovered from the raw materials, as observed in the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. The FPI was higher in total amino acids and essential amino acids (EAAs) compared with the original by-products ( p < 0.05). The alkali-aided process yielded a higher nutritional and color quality than the acidic process. Furthermore, we found that alkali-aided protein had higher oxidative stability than the acid-aided protein. Our study indicates that high-quality fish proteins can be efficiently recovered from low-value silver carp processing by-products using isoelectric solubilization/precipitation, particularly the alkali-aided process, and subsequently be used in value-added human foods.